Pendampingan dan Pengembangan Media Pembelajran Ofline dalam Implementasi Kurikulum Meredeka Belajar - Dokolamo, Hamid; Pinoa, Wiclif Sephnath; Sihasale, Daniel Anthoni (Universitas Pattimura, 2024)
This community service activity aims to support the implementation of the Merdeka Belajar Curriculum in schools with limited access to technology through assistance and development of offline learning media. This program involves training and workshops for teachers to improve their understanding of the Merdeka Belajar Curriculum and their ability to develop and use creative and effective offline learning media. The results of this activity show an increase in teacher competence in implementing the curriculum, developing various innovative offline learning media such as learning modules, educational posters, and simple teaching aids, as well as preparing learning plans that are more adaptive to local conditions. In addition, interesting and interactive offline learning media have succeeded in increasing student participation and interest in learning. The evaluation of this activity indicates that assistance and development of offline learning media is a strategic step in improving the quality of education in areas with limited access to technology, so that it can contribute to equalizing the quality of education throughout Indonesia.